2015
DOI: 10.1245/s10434-015-4544-x
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic Long-Term Results of Robot-Assisted Minimally Invasive Thoraco-Laparoscopic Esophagectomy with Two-Field Lymphadenectomy for Esophageal Cancer

Abstract: BackgroundOpen transthoracic esophagectomy is the worldwide gold standard in the treatment of resectable esophageal cancer. Robot-assisted minimally invasive thoraco-laparoscopic esophagectomy (RAMIE) for esophageal cancer may be associated with reduced blood loss, shorter intensive care unit (ICU) stay, and less cardiopulmonary morbidity; however, long-term oncologic results have not been reported to date.MethodsBetween June 2007 and September 2011, a total of 108 patients with potentially resectable esophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
114
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(124 citation statements)
references
References 30 publications
8
114
1
1
Order By: Relevance
“…The left gastric and short gastric vessels are divided and the gastroepiploic arcade preserved in its entirety during gastric mobilization. Near infrared fluorescence imaging with indocyanine green may be utilized to clearly identify and preserve the gastroepiploic arcade to its termination point (15). In the setting of previous induction chemoradiation therapy, an omental flap based off of 2-3 omental perforating arteries may be harvested for later reinforcement of the gastroesophageal anastomosis.…”
Section: Abdominal Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The left gastric and short gastric vessels are divided and the gastroepiploic arcade preserved in its entirety during gastric mobilization. Near infrared fluorescence imaging with indocyanine green may be utilized to clearly identify and preserve the gastroepiploic arcade to its termination point (15). In the setting of previous induction chemoradiation therapy, an omental flap based off of 2-3 omental perforating arteries may be harvested for later reinforcement of the gastroesophageal anastomosis.…”
Section: Abdominal Approachmentioning
confidence: 99%
“…Larger single institution series, including from Memorial Sloan Kettering Cancer Center and others, have reported systematic approaches in the development of a robotic assisted minimally invasive esophagectomy (RAMIE) program yielding excellent outcomes with increasing proficiency over the course of the learning curve (13)(14)(15). The primary purported benefit of the robotic assisted approach largely centers around the markedly increased control over the conduct of the operation afforded to the operator over open or alternative minimally invasive operations.…”
Section: Introductionmentioning
confidence: 99%
“…The Utrecht group, one of the pioneers in this field, reported that, based on 108 cases, their radical resection (R0) rate was 95%, 5‐year overall survival (OS) was 42%, and locoregional recurrence was only 6% 39. The Yonsei group, another pioneer, also reported R0 and 3‐year OS rates of 95.7% and 85%, respectively 40.…”
Section: Oncological Long‐term Resultsmentioning
confidence: 99%
“…In recent years, the usefulness and feasibility of robotic transthoracic esophagectomy for esophageal cancer have been reported. 79,80) Sluis et al 80) reported that robot-assisted minimally invasive thoracolaparoscopic esophagectomy for esophageal cancer has good local control with a low percentage of local recurrence on long-term follow-up. With regard to robotassisted esophagectomy, the further accumulation of patients or a randomized control study will be needed before worldwide adoption.…”
Section: Future Prospects Of Esophageal Cancer Treatmentmentioning
confidence: 99%